Intraoperative prediction of cardiac surgery-associated acute kidney injury using urinary biomarkers of cell cycle arrest - Cummings, Jared J; Shaw, Andrew D; Shi, Jing; Lopez, Marcos G; O'Neal, Jason B; Billings, 4th, Frederic T (The Journal of thoracic and cardiovascular surgery, 2019)
Tissue inhibitor of metalloproteinases 2 (TIMP-2) and insulin-like growth factor-binding protein 7 (IGFBP7) are postoperative urinary biomarkers of renal stress and acute kidney injury (AKI). We conducted this study to test the hypothesis that intraoperative concentrations of urinary [TIMP-2]·[IGFBP7] are associated with postoperative AKI. We measured urinary [TIMP-2]·[IGFBP7] at 8 perioperative timepoints in 400 patients who participated in a randomized controlled trial of atorvastatin for AKI in cardiac surgery. We compared [TIMP-2]·[IGFBP7] between subjects who did and did not develop KDIGO stage 2 or 3 AKI within 48 hours of surgery, adjusted for AKI risk factors. Fourteen patients (3.5%) met the primary endpoint of stage 2 or 3 AKI within 48 hours of surgery, and an additional 77 patients (19.3%) developed stage 1 AKI. Patients who developed stage 2 or 3 AKI displayed bimodal elevations of [TIMP-2]·[IGFBP7], with a first elevation (median, 0.45 [ng/mL] /1000) intraoperatively and a second elevation (1.45 [ng/mL] /1000) 6 hours postoperatively. Patients who did not develop AKI did not have any elevations in [TIMP-2]·[IGFBP7]. Each 10-fold increase in intraoperative [TIMP-2]·[IGFBP7] was independently associated with a 290% increase in the odds of stage 2 or 3 AKI (P = .01), and each 10-fold increase in the 6 hours postoperative [TIMP-2]·[IGFBP7] was independently associated with a 650% increase in the odds of stage 2 or 3 AKI (P < .001). The maximum [TIMP-2]·[IGFBP7] between these 2 timepoints provided an area under the receiver operating characteristic curve of 0.82 (95% confidence interval [CI], 0.73-0.90), 100% sensitivity, and 100% negative predictive value using the >0.3 cutoff to predict stage 2 or 3 AKI. Intraoperative elevations of [TIMP-2]·[IGFBP7] can predict moderate or severe AKI and could provide an opportunity to alter postoperative management to prevent kidney injury.